Antibacterial potential and chromatographic profiling of bioactive compounds from endophytic Streptomyces sp. strain MIRK71 isolated from Mirabilis jalapa (L.) - Lalrokimi; Purbajyoti Deka; William Carrie; Lallawmsangi; Christine Vanlalbiakdiki Sailo; Lalrosangpuii; Felicia Lalremruati; Awmpuizeli Fanai; Yasangam Umbon; Esther Lalnunmawii; Zothanpuia (PeerJ, 2025)
Multidrug-resistant bacteria pose an alarming global health threat. The persistent rise in antibiotic-resistant infections continues to challenge healthcare systems worldwide. This study aims to evaluate the antimicrobial potential of 18 endophytic actinobacteria isolated from Mirabilis jalapa (L.) against clinically relevant multidrug-resistant pathogens. Among these, strain MIRK71 exhibited the strongest activity in secondary antimicrobial screening and was selected for further investigation. Molecular characterization using 16S rRNA gene sequencing identified MIRK71 as a Streptomyces species. Morphological analysis via scanning electron microscopy (SEM) revealed branched, filamentous colonies with microspore chains. Antimicrobial compounds were extracted from the culture filtrate grown in ISP1 broth using methanol under reduced pressure in a rotary evaporator. Gas chromatography-mass spectrometry (GC-MS) analysis detected 20 volatile compounds. Further profiling was conducted using high-performance thin-layer chromatography (HPTLC) with three optimized solvent systems: ethyl acetate:methanol:water (20:3:2) for glycosides (SS1), cyclohexane:ethyl acetate:formic acid (4:6:1) for phenols (SS2), and toluene:ethyl acetate:methanol:acetic acid (3:5:1:0.5) for anthracenes (SS3). Five peaks were recorded in SS1 and SS3, while seven peaks were observed in SS2 at 254 nm. Overall, this study contributes to the growing body of knowledge on endophytic actinobacteria and underscores their potential applications in antimicrobial therapy.